Morse indices of solutions for super-linear elliptic PDE's. (April 2015) - Hajlaoui, Hatem; Harrabi, Abdellaziz; Mtiri, Foued
Abstract: In this paper, we establish L ∞ estimates for solutions of some general superlinear and subcritical elliptic equations via the Morse index. Our results generalize and improve the previous works (Bahri and Lions, 1992; Yang, 1998).